2022
DOI: 10.1002/hep.32344
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma progression depends on the uptake and metabolization of extracellular lipids

Abstract: Background and Aims: Cholangiocarcinoma (CCA) includes a heterogeneous group of biliary cancers with a dismal prognosis. We investigated if lipid metabolism is disrupted in CCA and its role in tumor proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
(95 reference statements)
0
17
0
Order By: Relevance
“…74 Additionally, in vitro and in a mouse model of AKT/NICD-driven cholangiocarcinogenesis, FASN and de novo lipogenesis were not required. 74,76 In contrast, CCA cells expressing low levels of FASN displayed high expression of FA uptake-related proteins and robust long-chain FA uptake, as a compensatory mechanism. Specifically, Li, Che, et al, 74 identified a role for FATP1 (SLC27A1), a member of the FA transport protein family.…”
Section: Cca and Lipid Metabolismmentioning
confidence: 99%
“…74 Additionally, in vitro and in a mouse model of AKT/NICD-driven cholangiocarcinogenesis, FASN and de novo lipogenesis were not required. 74,76 In contrast, CCA cells expressing low levels of FASN displayed high expression of FA uptake-related proteins and robust long-chain FA uptake, as a compensatory mechanism. Specifically, Li, Che, et al, 74 identified a role for FATP1 (SLC27A1), a member of the FA transport protein family.…”
Section: Cca and Lipid Metabolismmentioning
confidence: 99%
“…Notably, we observed a trend towards a reduction in HexCer and LacCer expression in G3 compared with G2 iCCA-derived EVs. Like other tumors, CCA is highly dependent on lipid and glucose metabolism [22,37]. Thus, similarly to the highly proliferative CCA cell lines, that are dependent upon increased lipid uptake and metabolization via fatty acid oxidation [22], poorly-differentiated tumors may require more glucose than the moderatelydifferentiated ones to sustain their metabolic demand.…”
Section: Discussionmentioning
confidence: 99%
“…Like other tumors, CCA is highly dependent on lipid and glucose metabolism [22,37]. Thus, similarly to the highly proliferative CCA cell lines, that are dependent upon increased lipid uptake and metabolization via fatty acid oxidation [22], poorly-differentiated tumors may require more glucose than the moderatelydifferentiated ones to sustain their metabolic demand. Therefore, the degradation of glycated ceramides could represent an additional source of glucose which could account for the accumulation of Cer, eventually removed by EVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations